Financial Contracting and Leverage Induced Over- and Under-Investment Incentives - Berkovitch, Elazar; Kim, E. Han (Journal of Finance, 1990)
This paper investigates the effects of seniority rules and restrictive dividend convenants on the over- and under-investment incentives associated with risky debt. We show that increasing seniority of new debt decreases the incidence of under-investment but increases over-investment, and vice versa. Under symmetric information, the optimal seniority rule is to give new debtholders first claim on a new project without recourse to existing assets (i.e., project financing). Under asymmetric information, the optimal debt contract requires equating the expected return to new debtholders in the default state to the new project's cash flow in the same rate. If this is not possible, the optimal seniority rule calls for strict subordination of new debt if the expected cash flow in default is small and full seniority if it is large. With regard to dividend convenants, we show that their effect depends on whether or not dividend payments are conditioned on future investments. When they are unconditioned, allowing more dividends increases the under-investment incentive. In contrast, conditional dividends decrease the underinvestment incentive and increase the over-investment incentive.